Effect of Jeevamrut on growth and quality of african marigold (Tagetes erecta L.) - PARMAR, RANJIT J.; WANKHADE, VISHAL R.; NANDRE, B. M.; K., MANANI PRITESH (Journal of Ornamental Horticulture, 2025)
An experiment titled "Effect of jeevamrut on growth and quality of African marigold (Tagetes erecta L.)" was conducted during Rabi 2023 at the College of Horticulture, S. D. Agricultural University, Jagudan, Gujarat, India. In this study Randomized Block Design was used a with three replications and evaluated sixteen treatments i.e. Control (T1), Jeevamrut drenching @ 500 l/ha (T2), 750 l/ha (T3), 1000 l/ha (T4), 5% Jeevamrut foliar application (T5), 10% (T6), 15% (T7), combinations of drenching and foliar application at various rates were used (T8 to T16). The treatment T13 (Jeevamrut drenching @ 750 l/ha + 15% foliar application) showed superior results in growth parameters with maximum plant height at 90 DAT (68.47 cm) and 120 DAT (74.21 cm), number of primary branches at 90 DAT (12.53) and 120 DAT (13.47) and plant spread (N-S) (43.97 cm), (E-W) (43.94 cm) and quality parameter with diameter of flower (7.00 cm) and weight of flower (6.81 g).